1984
DOI: 10.1177/028418518402500402
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Reduction of Childhood Intussusception

Abstract: The value of glucagon to facilitate hydrostatic reduction of childhood ileo-colic intussusception was tested in a series of 188 consecutive cases. Sixty-nine patients selected at random received 0.05 mg glucagon/kg body weight intramuscularly before attempts at reduction were started. The rate of successfully accomplished reductions was 84 per cent in the test group and 76 per cent in the control group (not significant). The time for accomplished reduction was approximately equal in the two groups. After 3 uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Glucagon has muscle relaxant effects as well as Buscopan, and has been used for enema reduction. In earlier reports, the reduction rate was higher when Glucagon was used 80,82 (level 3b); however, more recent randomized controlled studies have shown that glucagon is of no benefit 84,85 (level 2b). The use of glucagon is not recommended as it is an expensive drug in comparison to Buscopan, and health insurance in Japan may not cover the fee.…”
Section: Treatmentmentioning
confidence: 93%
“…Glucagon has muscle relaxant effects as well as Buscopan, and has been used for enema reduction. In earlier reports, the reduction rate was higher when Glucagon was used 80,82 (level 3b); however, more recent randomized controlled studies have shown that glucagon is of no benefit 84,85 (level 2b). The use of glucagon is not recommended as it is an expensive drug in comparison to Buscopan, and health insurance in Japan may not cover the fee.…”
Section: Treatmentmentioning
confidence: 93%
“…We included six RCTs with a total of 822 participants (Essa 2011;Franken 1983;Hadidi 1999;Lin 2000;Meyer 1993;Mortensson 1984), and we identified three ongoing trials (El Fiky 2016; Mehraeen 2011; Zhang 2015).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Two of the seven remaining publications were duplicates; thus we included them as one trial (Lin 2000). In summary, we included six RCTs (Essa 2011;Franken 1983;Hadidi 1999;Lin 2000;Meyer 1993;Mortensson 1984) in the review. These six completed trials were published in five di erent journals.…”
Section: Cochrane Database Of Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our institution does not use sedation during enema reduction attempts; however, the literature lacks conclusive data about the efficacy of sedation in aiding attempts at enema reduction. 6,[13][14][15][16] There was a 14.1% referral rate (n ¼ 19) for our intussusception patients, for which patients initially diagnosed at a referring institution were transferred to our hospital for definitive care. These transfers from the community predispose these patients to a longer duration of symptoms and delay in intervention which may affect success of a primary reduction, although data are inconsistent in determining if longer duration of symptoms affects the rate of successful enema reduction.…”
Section: Discussionmentioning
confidence: 99%